Jenderal M. Jusuf : panglima para prajurit - Sumarkidjo, Atmadji, 1952- (Jakarta : Kata Hasta Pustaka, 2006)
Biography of General M. Jusuf, d. 7 Sept. 2004, former Commander-in-Chief of the Indonesian Armed Forces and Minister for Defense and Security
Kepustakaan : p. 449-452 and index
Keywords: Jusuf, M. -- Biography; Military history -- Indonesia; Indonesia -- Politics and government -- History